2019
DOI: 10.3892/or.2019.6970
|View full text |Cite
|
Sign up to set email alerts
|

Momelotinib sensitizes glioblastoma cells to temozolomide by enhancement of autophagy via JAK2/STAT3 inhibition

Abstract: Temozolomide (TMZ) is a widely used chemotherapeutic agent for glioblastoma multiforme (GBM). However, chemoresistance to TMZ is still a major obstacle for GBM patients. An abundance of candidates has been reported to improve the chemotherapeutic sensitization of TMZ. In the present study, it was demonstrated that momelotinib (MTB) enhanced the sensitivity of glioma cells to TMZ in vitro, as evidenced by a noticeable decrease in cell growth and a significant increase in apoptosis and autophagy following treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…These tumor inhibitory and tumor microenvironment normalizing effects of pacritinib could be attributed to the suppression of STAT3/JAK2 signaling. Our observations were supported by a recent report that the inhibition of the JAK/STAT3 pathway resulted in disrupted intercellular communications between microglia and GBM cells [35] and pronounced anti-GBM effects [36,37]. In addition, we found that pacritinib treatment was able to suppress the number of miR-21-enriched exosomes secreted by GAMs.…”
Section: Discussionsupporting
confidence: 89%
“…These tumor inhibitory and tumor microenvironment normalizing effects of pacritinib could be attributed to the suppression of STAT3/JAK2 signaling. Our observations were supported by a recent report that the inhibition of the JAK/STAT3 pathway resulted in disrupted intercellular communications between microglia and GBM cells [35] and pronounced anti-GBM effects [36,37]. In addition, we found that pacritinib treatment was able to suppress the number of miR-21-enriched exosomes secreted by GAMs.…”
Section: Discussionsupporting
confidence: 89%
“…This tumor inhibitory and tumor microenvironment normalizing effects of pacritinib could be attributed to the suppression of STAT3/JAK2 signaling. Our observations were supported by a recent report that the inhibition of JAK/STAT3 pathway resulted in the disrupted intercellular communications between microglia and GBM cells [35] and pronounced anti-GBM effects [36,37]. In addition, we found that pacritinib treatment was able to suppress the number of miR-21-enriched exosomes secreted by GAMs.…”
Section: Discussionsupporting
confidence: 90%
“…Regulating autophagy was the key process involved in the chemoresistance and radioresistance of GBM . Sensitizing GBM cells to temozolomide via regulating autophagy has been widely reported by scholars . With respect to the interplay between autophagy and AS, splicing autophagy‐related genes has been reported to influence autophagy .…”
Section: Discussionmentioning
confidence: 99%